2020
DOI: 10.48193/rmu.v80i4.663
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer management challenges due to COVID-19 in countries with low-to-middle-income economies: A radiation oncology perspective

Abstract: Description: The COVID-19 pandemic poses an unprecedented challenge for urologic oncology and radiotherapy. Radiation oncology departments and international collaboration groups are sharing their management adaptations made in response to the pandemic. The present narrative review summarizes the current recommendations. Relevance:  There is a need to define which patients are candidates for safe treatment delay until the pandemic is over or controlled, to reduce exposure to the virus in the healthcare pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Six papers (all of them being either narrative reviews or consensus-based recommendations) addressed the role of active surveillance (AS) in PCa patients and concluded that in very low risk (VLR), low risk (LR), and favorable intermediate risk (FIR) PCa patients, AS is an adequate management strategy [20,24,27,29,30]. For LR and FIR patients, Rodriguez-Sanchez et al and Caicedo-Martinez et al suggest implementation of AS while delaying RP and RT until the pandemic is controlled [27,30], and Kokorovic et al suggest either AS or delaying RP up to 12 months [20]. Detti et al recommend multi-parametric MRI (mpMRI) of the prostate instead of re-biopsy in patients on AS [28].…”
Section: Active Surveillance In Pcamentioning
confidence: 99%
See 4 more Smart Citations
“…Six papers (all of them being either narrative reviews or consensus-based recommendations) addressed the role of active surveillance (AS) in PCa patients and concluded that in very low risk (VLR), low risk (LR), and favorable intermediate risk (FIR) PCa patients, AS is an adequate management strategy [20,24,27,29,30]. For LR and FIR patients, Rodriguez-Sanchez et al and Caicedo-Martinez et al suggest implementation of AS while delaying RP and RT until the pandemic is controlled [27,30], and Kokorovic et al suggest either AS or delaying RP up to 12 months [20]. Detti et al recommend multi-parametric MRI (mpMRI) of the prostate instead of re-biopsy in patients on AS [28].…”
Section: Active Surveillance In Pcamentioning
confidence: 99%
“…For low-and intermediate-risk PCa patients, all publications agree on active surveillance and delay of any modality of treatment [18,[20][21][22][23][24][25][26][27][28][29][30]34,39,40]. For highrisk patients and locally advanced disease, 3 systematic reviews [18,34,42] conclude that if primary curative RT is planned, delay between 1 and 3 months is feasible.…”
Section: Radiation Therapy In Pcamentioning
confidence: 99%
See 3 more Smart Citations